Buccal bifurcation cyst as an incidental finding in cone beam computed tomography scans - Anne Caroline OENNING; Luciana Butini OLIVEIRA; José Luiz Cintra JUNQUEIRA; Saulo L. SOUSA MELO (Faculdade São Leopoldo Mandic, 2018)
Buccal bifurcation cyst is an unusual inflammatory odontogenic cyst of unknown etiology which occurs at the buccal region of the permanent mandibular first molars in children and adolescents aged 6-15 years old. The aim of this manuscript is to present two clinical cases of buccal bifurcation cyst incidentally detected in adolescents referred for tomographic exams (CBCT) as part of the treatment planning for the management of impacted mandibular molars. The first case is very interesting due to the proximity of the lesion to the inferior alveolar canal. In the second case the inferior alveolar canal was not in close proximity to the lesion, but in contact with the mesiobuccal root of the second molar. The diagnosis of Buccal bifurcation cyst is of utmost importance in order to avoid complications during surgical procedures. In addition, the present case reports have highlighted the importance for dental practitioners to be aware of the possibility of a buccal bifurcation cyst being present as an incidental finding in CBCT images, especially in young patients.